Podcasting and constructive journalism in health stories about antimicrobial resistance (AMR). Issue 1 (May 2023) - Lindgren, Mia; Jorgensen, Britta
COVID-19 showed the importance of trustworthy and accessible health information. News organisations increasingly introduced podcasting to keep their audiences informed. Podcasting's documented capacity for listener engagement makes it a pertinent medium to study another global public health threat – superbugs – through the lens of constructive journalism. Both constructive journalism and podcasting feature lived experiences of sources, in constructive journalism focused on empowering audiences to act. This practice-led research study is the first to explore how solutions-oriented journalism intersects with narrative podcasts. It demonstrates through the production of a podcast series about antimicrobial resistance (AMR), an affordance to tell complex and often scary health stories. It finds that podcasting can position individuals affected by AMR as sources of empowering information, rather than as victims. The study contributes new knowledge to constructive podcast journalism as an impactful approach in public health journalism, leveraging its potential to provide solutions to listeners and promote change.